Recent Research and Advances in Soilless Culture - Turan, Metin; Argin, Sanem; Yildirim, Ertan; Güneş, Adem (IntechOpen, 2023)
Due to the world's increasing population, the demand for food is rapidly growing. There is a real concern that we are headed toward a food crisis. Land for farming is dwindling, leading to the need to develop alternative production methods. One of the most promising is soilless agriculture, which refers to growing crops, particularly horticultural crops, in different growing media or in substrates other than soil (substrate culture) or in aerated nutrient solutions (water culture). The primary advantage of soilless agriculture is that it is independent of the negative effects of climate change and chemical pollution (temperature and soil intensity variations, drought, salinity, soil degradation, low biodiversity, toxicity, and diseases). This book presents up-to-date information on soilless culture types, how to manage plant nutrition, fertilizer use, organic cultivation, plant diseases and plant protection in soilless agriculture, the use of smart agricultural tools, the evaluation of carbon and water footprint, and the economic aspects of soilless agriculture.